Soil Physical Properties and Oil Palm Plant (Elaeis guineensis Jacq.) Growth Applied with Solid Waste of Palm Oil Mill - Asman Sarif Daulay; Nelvia Nelvia; Adiwirman Adiwirman (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2022)
The growth of oil palm plants, such as height, additional fronds, and stem diameter, depends on the soil condition and its physical properties. Good soil physical properties will support the growth of oil palm plants. On marginal lands such as ex-mining land and sub-soil soil that has poor soil physical properties, improvements must be made. Thus, palm oil cultivation on ex-mining land or subsoil land can grow well. This research aims to study solid application to various soil conditions to improve the growth and physical properties of oil palm plants. The land applied by solid is an ex-mining land subsoil land. Meanwhile, the land with flat topography has not been degraded as a control. The data analysis carried out is an orthogonal contrast test, between control with solid application and without solid application, between solid application with without solid, between among solid application (ex-mining and subsoil land), between among without solid application (ex-mining and subsoil land). The research result shows that soil physical properties and plant growth applied with solid are better than without solid, lower bulk density value, higher total pore space and water holding capacity, taller plant growth, higher palm branches quantity, larger stem diameter. Solid application in ex-mining is lower than solid application on sub-soil, with lower water holding capacity value and lesser palm fronds addition. Without solid application on ex-mining sites, the results are worse than no solid application on sub-soil, with lower water holding capacity and lower plant height. Control is better than solid and without solid applications, higher plants, higher addition of frond quantity, and larger stem diameter.